The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1017/s104161020800817x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and diagnostic profile of patients seeking dementia care in a memory clinic in Hong Kong

Abstract: Dementia patients in Hong Kong apparently enjoy a long subclinical period and only seek medical attention at late stages. Local Chinese culture and socioeconomic backgrounds could be the main reasons that underlie these observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
35
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 31 publications
10
35
5
Order By: Relevance
“…In our study, AD was the most common dementia subtype (38.3%), followed by VaD (25.4%); this is consistent with hospital-based studies from different parts of the world [5,9,15,16,35]. Among VaD subtypes, subcortical VaD was the most common and it was present in nearly half of patients, consistent with previous reports [32].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In our study, AD was the most common dementia subtype (38.3%), followed by VaD (25.4%); this is consistent with hospital-based studies from different parts of the world [5,9,15,16,35]. Among VaD subtypes, subcortical VaD was the most common and it was present in nearly half of patients, consistent with previous reports [32].…”
Section: Discussionsupporting
confidence: 92%
“…The mean age of dementia patients in developed countries is between 73 and 80 years, in contrast to the 66.3 years reported in our study [5,9,14,15,35]. This finding is probably a reflection of the demographic profile of India.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…Kochunov et al [19] found anatomical differences in the frontal, temporal and parietal gyri between Chinese and English speakers, which might be due to neural plasticity. Compared with English speakers, native Chinese have also been reported to behave differently in psychological and epidemiological studies [20,21,22,23]. Thus, it is reasonable for native Chinese speakers with SCA3 to develop unique cognitive impairments that differ from those of their English-speaking counterparts.…”
Section: Introductionmentioning
confidence: 99%